1996
DOI: 10.1093/qjmed/89.10.789
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an infection consultation service for bacteraemia on clinical management and use of resources

Abstract: Since 1993, the infection consultation service for bacteraemia has seen 310 patients in the Medical and Surgical Directorates at Ninewells Hospital and Kings Cross Hospital. A random sample of 100 was audited. Case-notes were incomplete for five patients, leaving 95 fully-audited patients. Clinical outcome measures were death from infection, and readmission within 2 weeks of discharge. Initial treatment was inconsistent with antibiotic policy in 46 patients (48%). Antibiotic treatment was changed in 37 (80%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…[18]. In a number of pre-and post-intervention comparisons, some of the proposed strategies and the implementation of guidelines have been reported as successful in reducing inadequate drug prescribing and expenses for antimicrobials [19][20][21][22][23][24][25][26][27]. However, true cost savings have been difficult to estimate given the multiplicity of confounding variables and the lack of control data of cost variation over time.…”
Section: Introductionmentioning
confidence: 99%
“…[18]. In a number of pre-and post-intervention comparisons, some of the proposed strategies and the implementation of guidelines have been reported as successful in reducing inadequate drug prescribing and expenses for antimicrobials [19][20][21][22][23][24][25][26][27]. However, true cost savings have been difficult to estimate given the multiplicity of confounding variables and the lack of control data of cost variation over time.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have addressed the profound value of these consultations regarding infectious complications in the inpatient setting [8,[11][12][13][14][15][16][17][18][19]. To the best of our knowledge, this is the first study to address the impact of ID specialist consultations in an outpatient setting in a comprehensive cancer center, an area where the literature is scarce [9,20].…”
Section: Discussionmentioning
confidence: 98%
“…The median number of evaluations per patient was two (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], which was almost equal to that in a series of outpatients reported by Grupper and Potasman [9]. In the most comprehensive study performed on a larger scale, Yinnon [17] suggested that an average of one or two follow-up visits after the first ID specialist consultation is optimal and that the impact of subsequent visits decreases; likely exceptions to this are consultations regarding critically ill patients in intensive care, hematology, and transplantation units.…”
Section: Discussionmentioning
confidence: 99%
“…Die Mor ta li tät der Sep sis nahm in den letz ten 2-3 De ka den dras tisch ab [5,10,11,12,13,14]. In ei ner ei ge nen Stu die wur den 103 Pa ti en ten mit ei ner Sep sis un ter sucht.…”
Section: In Fek Tio Lo Gi Sche Er Fol Ge Bei Der Sep Sisunclassified